Sustainable Career Development: A new challenge in career counselling in the modern era - Argyropoulou, Katerina (Advances in Social Sciences Research Journal, 2021)
Sustainable Career Development constitutes an interdisciplinary research area in the field of counseling and career guidance that is based on Sustainable Development. In this context, the aim of the manuscript is to report the importance of providing career counselling to manage one’s personal and professional growth and development in a sustainable approach. In the framework of this effort, we are presenting the Sustainable Career Development Scale and putting forward a number of implications for career intervention, which relate to sustainability in career.